2021
DOI: 10.3390/cells10082012
|View full text |Cite
|
Sign up to set email alerts
|

Human Lung-Resident Macrophages Express and Are Targets of Thymic Stromal Lymphopoietin in the Tumor Microenvironment

Abstract: Thymic stromal lymphopoietin (TSLP) is a pleiotropic cytokine highly expressed by epithelial cells and several innate and adaptive immune cells. TSLP exerts its biological effects by binding to a heterodimeric complex composed of TSLP receptor (TSLPR) and IL-7Rα. In humans, there are two TSLP isoforms: the short form (sfTSLP), constitutively expressed, and the long form (lfTSLP), which is upregulated in inflammation. TSLP has been implicated in the induction and progression of several experimental and human ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 119 publications
(216 reference statements)
0
41
0
Order By: Relevance
“…Expression of TSLP protein in tumours was significantly higher than in benign lesions and non-cancer lung tissue, and the prevalence of regulatory T cells in the tumour microenvironment correlated with the expression of TSLP in lung cancer. Furthermore, TSLP and TSLPR are expressed in macrophages purified from the lungs of patients with lung cancer 145 , with a presumed pro-tumorigenic role for TSLP.…”
Section: Tslp and Cancermentioning
confidence: 99%
“…Expression of TSLP protein in tumours was significantly higher than in benign lesions and non-cancer lung tissue, and the prevalence of regulatory T cells in the tumour microenvironment correlated with the expression of TSLP in lung cancer. Furthermore, TSLP and TSLPR are expressed in macrophages purified from the lungs of patients with lung cancer 145 , with a presumed pro-tumorigenic role for TSLP.…”
Section: Tslp and Cancermentioning
confidence: 99%
“…VEGF-C and VEGF-D are key regulators of lymphangiogenesis by activation of the VEGFR3 receptor on lymphatic endothelial cells (LECs) [ 141 ]. Previous studies have demonstrated that tissue-resident immune cells, such as human macrophages [ 142 , 143 ] and mast cells [ 110 , 112 , 144 ], are a major source of lymphangiogenic factors. When we investigated the effects of sPLA 2 on the release of lymphangiogenic factors from human neutrophils, we found that these cells do not express VEGF-C/VEGF-D mRNAs.…”
Section: Neutrophils Angiogenesis and Lymphangiogenesismentioning
confidence: 99%
“…Macrophages, important resident immune cells in TME [ 143 , 262 ], are critical sentinels in tumor immunity, modulating angiogenesis and lymphangiogenesis [ 21 , 263 ] and surveilling against tumors [ 264 , 265 ]. Recent studies have demonstrated that activated macrophages can release extracellular DNA traps, also called macrophage extracellular traps (METs) [ 95 , 230 , 266 ].…”
Section: Nets and Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Exposing HLMs to lfTSLP stimulate these cells to produce proinflammatory and angiogenic factors (TNF-α), which can, in turn, promote lung cancer progression. This research indicates the importance of the TSLP system (via the selection of distinct TSLP isoforms) and underlines the ability of the lfTSLP, produced by HLMs, in directing the fate of lung cancer [8].…”
Section: Myeloid Cells and Their Multifaceted Roles In Tumor Progressionmentioning
confidence: 57%